Analisa Penyalahgunaan Media Sosial untuk Penyebaran Cybercrime di Dunia Maya atau Cyberspace - Yuni Fitriani; Roida Pakpahan (Universitas Bina Sarana Informatika, 2020)
Progress was technology that can make it easier to access information we need. But in its development, theprogression of the technology was also used as the emergence of opportunities cyber crime.Where is the moment, abuse ofsocial media is facilitating the spread of cybercrime in the cyberspace, As the emergence of cases defamation, cases of hatespeech, cases of hoax, fraud cases pretended to be the buying and selling of online, Online prostitution and the case other cybercrime. In the year 2018 more than 50 percent of evil siber derived from social media especially facebook and twitters. The research results show that abuse social media to the spread of cybercrime it is still going until now. Where most of an offender cybercrime in the media social either intentionally or unintentionally will be charged by The law No. 11 year 2008 on information and electronic transaction (UU ITE). Keywords: Social Media, Cybercrime, UU ITE